Fish to 2030 : Prospects for Fisheries and Aquaculture - World Bank (Washington, DC, 2014)
This report analyzes global prospects for fisheries and aquaculture. The World Bank Group (WBG) Agriculture Action Plan 2013-15 summarizes critical challenges facing the global food and agriculture sector. An ever-increasing global population necessitates adequate food and nutrition for the growing population through increased production and reduced waste. Production increase must occur in a context where resources necessary for food production, such as land and water, are even scarcer in a more crowded world, and thus the sector needs to be far more efficient in utilizing productive resources. The important issues addressed herein are: 1) health of global capture fisheries; 2) the role of aquaculture in filling the global fish supply - demand gap and potentially reducing the pressure on capture fisheries; and 3) implications of changes in the global fish markets on fish consumption, especially in China and Sub-Saharan Africa.